Correlation Between Non-insulin-Based Insulin Resistance Indices and Increased Arterial Stiffness Measured by the Cardio–Ankle Vascular Index in Non-hypertensive Chinese Subjects: A Cross-Sectional Study - Zhang, Xin; Ye, Runyu; Yu, Chaoping; Liu, Tianhu; Chen, Xiaoping (Frontiers in Cardiovascular Medicine, 2022)
Data are limited on the relationship between the cardio–ankle vascular index (CAVI) and non-insulin-based insulin resistance (IR) indices, including the triglyceride to high-density lipoprotein cholesterol ratio (TG/HDL-C), fasting triglyceride and glucose index (TyG), and metabolic score for IR (METS-IR). In this study, we explored the relationship between TG/HDL-C, TyG, METS-IR, and the risk of increased arterial stiffness (CAVI ≥8.0) and compared their ability to detect arterial stiffness in the non-hypertensive Chinese population. A total of 3265 non-hypertensive subjects were included. Spearman’s and partial correlation analyses were used to assess the relationship between non-insulin-based IR indices and CAVI. The correlation between these indices and the risk of a CAVI ≥8.0 was explored by multiple logistic regression analysis. The area under the receiver-operating characteristic curve was used to compare the ability of TG/HDL-C, TyG, and METS-IR to detect a CAVI ≥8.0. After adjustment for confounding factors, linear regression analysis showed that the CAVI changed by 0.092 (95% confidence interval [CI] 0.035–0.149) per standard deviation increase in TyG. While, this linear relationship was not found when analyzing TG/HDL-C and METS-IR. Multiple logistic regression analysis showed that the proportion of patients with CAVI ≥8.0 in the fourth quartile of TG/HDL-C (Q4 vs Q1: odds ratio [OR] 2.434, 95% CI 1.489–3.975), TyG (Q4 vs Q1: OR 2.346, 95% CI 1.413–3.896), and METS-IR (Q4 vs Q1: OR 2.699, 95% CI 1.235–5.897) was significantly higher than that in the lowest quartile. The area under the curve that could discriminate CAVI ≥8.0 was 0.598 (95% CI 0.567–0.629) for TG/HDL-C, 0.636 (95% CI 0.606–0.667) for TyG, and 0.581 (95% CI 0.550–0.613) for METS-IR. In this study, we demonstrated a significant association between increased arterial stiffness and non-insulin-based IR indices. Among them, TyG showed better discriminatory ability than TG/HDL-C or METS-IR.